Industrial Rotary Kiln Burner Performance with 3D CFD Modeling - Duarte M. Cecílio; Margarida Mateus; Ana Isabel Ferreiro (Fuels, 2023)
As the need to minimize environmental impacts continues to rise, it is essential to incorporate, advance, and adopt renewable energy sources and materials to attain climate neutrality in industrial operations. It is established that economic growth is built upon infrastructure, where the cement industry plays a crucial role. However, it is also known that this industry is actively looking for ways to transition toward low-carbon practices to encourage sustainable and environmentally conscious practices. To this end, the use of refuse-derived fuels to substitute fossil fuels is very appealing, as these have the potential to lower clinker production costs and CO2 emissions. Bearing this in mind, the primary objective of this work is to gain insights into the combustion behavior in an industrial rotary kiln by studying real-life scenarios and to assess the potential of substituting alternative fuels for fossil fuels to reduce CO2 emissions. A 3D CFD turbulent combustion model was formulated in Ansys® considering a Pillard NOVAFLAM® burner, where refuse-derived and petcoke fuels were used, and different secondary air mass flows were considered. From the obtained results, it was possible to conclude that the outcome of the combustion process is greatly influenced by the fuel-to-air ratio. Increasing the secondary air mass flow promotes the occurrence of a complete and efficient combustion process, leading to enhanced fuel conversion and the decreased formation of pollutants such as CO, soot, and unburned hydrocarbons. An increase in combustion efficiency from 93% to 96% was observed, coupled with a slight decrease in the pollutant mass fraction in the flue gas.